Deletion of a Short, Untranslated Region Adjacent to the Polypurine Tract in Moloney Murine Leukemia Virus Leads to Formation of Aberrant 5′ Plus-Strand DNA Ends In Vivo - Bacharach, Eran (American Society for Microbiology, 2000)
Experiments were performed to determine the function of a 28-nucleotide untranslated sequence lying between the envelope gene and the polypurine tract (PPT) sequence in the Moloney murine leukemia virus (Mo-MuLV) genome. A mutant virus carrying a deletion of this sequence (Mo-MuLVΔ28) replicated more slowly than wild-type (wt) virus and reverted by recombination with endogenous sequences during growth in NIH 3T3 cells. We show that this deletion did not affect the level of viral protein expression or genomic RNA packaging. Mo-MuLVΔ28 served as a helper virus as efficiently as the wt virus; in contrast, a retroviral vector harboring this mutation exhibited reduced transduction efficiency, indicating that the mutation acts not in trans but in cis. Analysis of acutely infected cells revealed that reduced levels of viral DNA were generated by reverse transcription of the Mo-MuLVΔ28 RNA as compared to the wt RNA. Analysis of DNA circle junctions revealed that plus-strand DNA of Mo-MuLVΔ28 but not wt virus often retained the PPT and additional upstream sequences. These structures suggest that aberrant 5′ ends of plus-strand DNA were generated by a failure to remove the PPT RNA primer and/or by mispriming at sites upstream of the PPT. These data demonstrate that the major role of the sequences immediately upstream of the PPT is specifying efficient and accurate plus-strand DNA synthesis.